Historic analysis of habitat suitability for the commercially promising berry crop Kadsura longipedunculata in China under climate change - Kai Chen; Zhaoqi Xie; Binsheng Luo; Jiaxing Yang; Mingli Hu; Chunsong Cheng (PLoS ONE, 2025)
Climate change is threatening global plant diversity, necessitating the identification of resilient species for sustainable utilization. This study presents the first comprehensive prediction integrating paleo, current, and future climate scenarios with soil and terrain variables to assess Kadsura longipedunculata , a cold-tolerant evergreen liana with economic and medicinal values. Using 158 validated species occurrence records and 15 key environmental variables (climate, soil, and terrain), we employed the MaxEnt model integrated with ArcGIS to predict distribution shifts across the Last Glacial Maximum (LGM; ~ 22 kyr BP), Mid-Holocene (MH; ~ 6 kyr BP), current (1970–2000), and future periods (2041–2060, 2081–2100) under SSP126 and SSP585 scenarios. Our results revealed that precipitation during the driest month (bio14) was the most critical factor influencing habitat suitability, contributing 75.9% to the model. Under current conditions, highly suitable habitats were concentrated in southeastern China (25°N–30°N), particularly in Jiangxi, Fujian, and Hunan provinces. Future projections indicated significant restructuring: firstly total suitable area showed limited change under most scenarios (<±10%), but low-suitability habitats were showed contracting substantially (>20%) under SSP126-2050s and SSP585-2090s, while medium-suitability areas were showed expanding (up to +17.0%). High-suitability habitats were showed remaining stable, and a northward migration trend of distribution centroids, and highlights both the species’ resilience in core montane habitats and its vulnerability to precipitation changes. The findings offer a scientific basis for conserving and domesticating this species, with Jiangxi Province identified as a key region for future cultivation efforts.